AKTUALISASI KULIAH KERJA NYATA (KKN) DI DESA SONGKA BATU KAJANG ANGKATAN XIX KECAMATAN BATU SOPANG KABUPATEN PASER - Adiyono Adiyono; Ahmad Rais, Mila Oktavia, Nur Aisyah Musri, Siti Juhra, Muhammad Syarif Ilyasa, Kurniawati, Nirwana (Adiba Aisha Amira, 2022)
STIT Ibnu Rusyd Tanah Grogot students attend lectures in the real world as a way to develop their social skills, practice their knowledge and abilities, and contribute to the provision of life in the community where the service is provided. This study uses the phenomenological method in its qualitative field investigation. The phenomenon surrounding the implementation of Community Service Program in Songka Village, Batu Sopang District, is studied using a phenomenological approach. Observations, interviews, and documentation are used as data collection methods. Data processing and analysis techniques include data reduction, data presentation, and verification or drawing conclusions. The following are the findings of the Field Work Lecture (KKN) in Songka Village, Batu Batu Sopang District: First, it is known that Songka Village is a lowland location and the majority of the population works in the coal industry. Second, community governance is well organized. The three groups are religious because they participate in various rituals and religious activities, including teaching at several TPAs, BIMO (Bis Mufrodat), organizing the Sholeh Children's Festival in Songka Village in commemoration of the Isra Mi'raj day of 1443 H and others. The four KKN STIT Ibnu Rusyd Tanah Grogot in Songka Village ran efficiently and effectively. They are able to analyze and solve cross- sectoral community problems, assist the government in achieving development, and develop cadres in rural areas by making religion the basis and compass to launch and direct community activities.